2019
DOI: 10.1002/ajhb.23221
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of physical fitness in elementary school children: The role of changes in body fat

Abstract: Objectives The aim of the present study was to examine the stability of physical fitness, and the interrelationships among intra‐individual changes in fitness and fatness among elementary school children. Methods A longitudinal study was conducted among 372 adolescents (196 boys) and followed up over 3 years (from childhood to adolescence). Physical fitness was estimated using three indicators: cardiorespiratory fitness (through a 9‐minute running test), flexibility (through a sit‐and‐reach test), and muscle r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…The biological maturation (MO) was estimated through the somatic maturation method proposed by Werneck et al [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological maturation (MO) was estimated through the somatic maturation method proposed by Werneck et al [27].…”
Section: Discussionmentioning
confidence: 99%
“…Children performed an SBJ as per the field test guidelines. The biological maturation (MO) was estimated using the somatic maturation method proposed by Werneck et al [27]. Then, the age of PHV was determined by subtracting the MO from the chronological age.…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%
“…Ortega et al [14] found in a prospective study of about 600 normal-weight children over a duration of six years that improvements in fitness from childhood to adolescence are related with a reduced risk of becoming overweight or obese in adolescence. Werneck et al [15] recently reported convincing association between increases in body adiposity from childhood to adolescence and the reduction in physical fitness in a three-year longitudinal study including about 370 children. In addition, Greier and Drenowatz [16] showed in a four-year longitudinal study of more than 200 Austrian middle school students a bidirectional, inverse association between body weight and physical fitness.…”
Section: Introductionmentioning
confidence: 99%
“…This prospective study was initially designed to examine growth, maturation and physical fitness in schoolchildren aged 7 to 10 years recruited from a private school in Londrina (Paraná, Brazil), with a mixed longitudinal design with four birth cohorts (1992, 1993, 1994, 1995) followed annually from 2002 to 2006 (initial moment research approved by ethics committee of Campinas State process CEP N 249/2002, July 16, 2002, and longitudinal data by ethics committee of Londrina State University process CEP N 024/03, April 01, 2003). Criteria of sampling were an α of 95%, a statistical power of 80%, and an error of 5% as previously described [ 26 ]. Parents or legal guardians of 1052 children signed an informed consent, and participants were informed that their participation was voluntary.…”
Section: Methodsmentioning
confidence: 99%